2021
DOI: 10.2147/dmso.s312334
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Plasma Betaine in Middle Pregnancy Was Associated with Decreased Risk of GDM in Twin Pregnancy: A Cohort Study

Abstract: Purpose Although previous studies have shown that choline-related metabolites in one carbon metabolism (OCM) were related to gestational diabetes mellitus (GDM) risk in singleton pregnancy, their role in twin gestations remains unclear. We aimed to investigate the associations between choline, betaine, methionine, dimethylglycine (DMG), trimethylamine N-oxide (TMAO) and GDM risk among women with twin gestations. Patients and Methods This hospital-based cohort study incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Several one-carbon metabolites have been implicated in risk for GDM. Specifically, increasing concentrations of circulating folate [ 7 , 11 , 14 , 15 , 16 ] and homocysteine [ 113 , 120 , 121 , 122 , 127 ], and decreasing vitamin B12 [ 14 , 15 , 111 , 112 , 115 ] and betaine [ 175 , 176 , 177 ] associate with increased GDM risk. Excess intake of FA has emerged as a key risk factor in GDM development.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several one-carbon metabolites have been implicated in risk for GDM. Specifically, increasing concentrations of circulating folate [ 7 , 11 , 14 , 15 , 16 ] and homocysteine [ 113 , 120 , 121 , 122 , 127 ], and decreasing vitamin B12 [ 14 , 15 , 111 , 112 , 115 ] and betaine [ 175 , 176 , 177 ] associate with increased GDM risk. Excess intake of FA has emerged as a key risk factor in GDM development.…”
Section: Discussionmentioning
confidence: 99%
“…In a prospective cohort study ( n = 486), maternal plasma betaine (≤200 nmol/mL) in early pregnancy (median: 10 weeks’ gestation, IQR: 9–11) was associated with increased GDM risk (OR: 5.00 95% CI: 2.76–9.07) [ 175 ]. Similarly, in a cohort study of dichorionic twin pregnancies ( n = 187), plasma betaine had an inverse relationship with GDM risk ( p trend = 0.015) [ 176 ].…”
Section: Association Between One-carbon Metabolism Players and Gdmmentioning
confidence: 99%
See 1 more Smart Citation
“…Mothers with high plasma choline concentrations were shown to have a lower risk of these complications, but the results were not statistically significant. On the contrary, in a study [ 73 ] of women with twin pregnancies, they found no effect of maternal choline levels on the risk of GDM.…”
Section: Maternal Choline Deficiency and Adverse Pregnancy Outcomesmentioning
confidence: 81%
“…Sample preparation was conducted according to our previous study (Gong et al, 2021 ). Briefly, 50 μL of plasma was added into 30 μL of 0.1 M dithiothreitol, vortexed for 5 min, and then incubated for 10 min at room temperature.…”
Section: Methodsmentioning
confidence: 99%